Students’ perception, concentration, and attention in learning and teachers’ challenging approaches for effective and efficient learning: The social context, the influence of social networks, and technology have changed the learning environment and the need for new educational policies - Hysa, Ferit; Agani, Mentor (Edelweiss Applied Science and Technology, 2025)
This study is in the field of cognitive psychology and it focuses on the perception and attention of students in learning. The purpose of this study is to investigate the factors affecting the perception and concentration of students in learning, as well as the new contexts created with the development of technology. The perception and concentration of students in learning have changed, and distracting factors have increased. This study hypothesizes that high learning outcomes for students are achieved through interactive learning and new inclusive approaches. The study method is both quantitative and qualitative. For this, questionnaires are administered to a specific sample, and for the qualitative method, observations and interviews are conducted from which the necessary data are collected for analysis. The study population consists of all pre-university education students in Tirana, and the study sample is composed of three 9-year schools in the city of Tirana and three schools in the Elbasan region, totaling 5,400 students. The schools were selected by lot from a total of 112 schools in the city of Tirana and 23 schools in the Elbasan region. Data analysis is performed using the SPSS program, and for qualitative data, categorization and classification of the analyzed data are employed. The conclusion is that the factors of perception, concentration, and attention of students in teaching and learning have changed in favor of distraction, and teachers must ensure that learning builds different approaches to mitigate the distractions of perception and concentration.